The Development of Model to Enhance Teachers Competency in Research by Using Particippatory Action Research in Pattaya City School - ฉิมพลี, อิสริญญา; จิระโร, พงศ์เทพ; ลิลา, สมศักดิ์ (Journal of Graduate Research, 2017)
The objectives of this research were 1) to study the condition of doing research of Pattaya City Teachers, 2) to develop the model of enhancingteachers’ competency by participatory action research in Pattaya City Schools and 3) to evaluate the model of enhancing teachers’ competency by participatory action research in Pattaya City Schools. The research methodology was divided into 3 phases. First phase was to study the condition of doing research of the samples in Pattaya City school. The sample in this research were 231 teachers from 11 Schools in Pattaya City who were Stratified Random Sampling. The second phase was to create and develop the model by informing by 14 persons advisors. The third phase was to evaluate the model by 17 persons advisors.The research instruments were the questionnaire, focus group discussion form and evaluation form. The data analysis were Frequency, Percentage, the Average, Standard Deviation, the Priority Need Index (PNI),T-Test, One way ANOVA, Content Analysis, Median and Interquartile Range. The results of the study were as follows: The general knowledge of most teachers in Pattaya City Schools was low and their scores were less than 50 percent of full score. They have high attitude of doing the research whereas they could do the research in average rate. The expectation of doing research was very high rate and they wanted to develop their competency of doing research with very high rate. The condition of doing researchhave statistically significant difference at .05 The model of enhancing teachers’ competency by participatory action research in Pattaya City Schools was Participatory Action Research (PAR) with four processes: Plan, Action and Observe, Reflect and Input. The result of the evaluation of the model of enhancing teachers’ competency by participatory action research in Pattaya City Schools with the process of Participatory Action Research (PAR) was advantage, appropriateness, possibility and accuracywith very high rate.